Prevalence of stunting and overweight/obesity among Brazilian children according to different epidemiological scenarios: systematic review and meta-analysis - Sousa, Carolina Pereira da Cunha; Olinda, Ricardo Alves de; Pedraza, Dixis Figueroa (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Within the Brazilian nutritional panorama, coexistence of antagonistic nutritional disorders can be seen, especially the increasing prevalence of overweight and the persistence of significant rates of chronic malnutrition in vulnerable groups of the population. Because these are major public health problems, this study aimed to ascertain the prevalence of stunting and overweight/obesity among Brazilian children according to different epidemiological scenarios. DESIGN AND SETTING: This was a systematic review of prevalence studies, developed at the State University of Paraíba. METHODS: The SciELO, Lilacs and PubMed databases were searched for articles, using specific keywords. Articles published between 2006 and 2014 were selected. The review was conducted by two reviewers who worked independently. A systematic review with meta-analysis was conducted, for which the studies were grouped within different epidemiological settings. RESULTS: Among the 33 articles recovered, 9 involved samples from daycare centers, 4 had samples from public healthcare services or social registers, 5 related to populations in situations of social inequity and 15 were population-based. Higher chances of stunting were found in populations in situations of social inequity and in those at public healthcare services or on social registers, in relation to reference populations. For overweight/obesity, none of the scenarios had a higher chance than the reference. CONCLUSION: Among Brazilian children, stunting continues to be a socially determined public health problem that mainly affects marginalized populations. This problem coexists with significant rates of overweight/obesity affecting all social groups.